AN EXAMINATION OF THE IMPLEMENTATION OF INTERNET OF THINGS IN HEALTHCARE UTILIZING SMARTWATCHES - Fatemeh Sadeghi Boshrabadi; Moussa Abolhassani; Shadi Shafaghi; Fariba Ghorbani; Masoud Shafaghi (Jurnal Administrasi Kesehatan Indonesia)
Background: Smartwatches can use sensors to collect and send data to medical teams and family members through the platform of the Internet of things (IoT). The data are first analysed on the platform and the final results are used by the medical team.